2015
DOI: 10.1108/nlw-04-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

The librarianship portfolio

Abstract: Purpose – This paper aims to describe the development of a Librarianship Portfolio for the purposes of permanent status evaluation and rank promotion at a small private university with a unionized faculty. Design/methodology/approach – The Librarianship Portfolio was conceived and based on teaching portfolios and evaluative documents at other colleges and universities and is also a direct result of collective bargaining negotiations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Perhaps unsurprisingly, instructional librarians are most often the subject of extant literature. Most accounts of teaching portfolio creation detailed an approach that embraced the portfolio as process and product oriented, blending formative and summative approaches (Fast and Armstrong 2003;McCallon 2006;Mills 2015;Parker and Hillyer 2008). Academic librarians have been among those early adopters of "course portfolios" for individual course assessment (Fast and Amstrong 2003) and among the first at their institutions to adapt the teaching portfolio to their professional context, a trend the authors believe extends to the activities detailed in this article.…”
Section: Mots-clés : Bibliothéconomie Universitaire • éValuation Du C...mentioning
confidence: 95%
See 1 more Smart Citation
“…Perhaps unsurprisingly, instructional librarians are most often the subject of extant literature. Most accounts of teaching portfolio creation detailed an approach that embraced the portfolio as process and product oriented, blending formative and summative approaches (Fast and Armstrong 2003;McCallon 2006;Mills 2015;Parker and Hillyer 2008). Academic librarians have been among those early adopters of "course portfolios" for individual course assessment (Fast and Amstrong 2003) and among the first at their institutions to adapt the teaching portfolio to their professional context, a trend the authors believe extends to the activities detailed in this article.…”
Section: Mots-clés : Bibliothéconomie Universitaire • éValuation Du C...mentioning
confidence: 95%
“…Existing scholarship is diminutive on the topic of academic librarians and teaching portfolios, with scant accounts of teaching portfolio creation among "noncanadian journal of academic librarianship revue canadienne de bibliothéconomie universitaire instructional" librarians. The authors identified four articles published about noninstructional academic librarian teaching portfolio creation from universities in the United States (McCallon 2006;Mills 2015;Sterling et al 2022;vanDuinkerken, Coker and Anderson 2010). Perhaps unsurprisingly, instructional librarians are most often the subject of extant literature.…”
Section: Mots-clés : Bibliothéconomie Universitaire • éValuation Du C...mentioning
confidence: 99%